PENERAPAN TEKNIK SELF-DISCLOSURE UNTUK MENINGKATKAN KOMUNIKASI INTERPERSONAL DALAM PEMBELAJARAN PAI DI SMP AL-HASRA DEPOK - Nur Hidayati, Insani; Tuti Rahmawati, Sri (Menara Tebuireng, 2025)
Abstract— This study discusses the implementation of the self-disclosure technique in Islamic Religious Education (PAI) learning and how it enhances students’ interpersonal communication skills. Effective learning should not only focus on cognitive development but also on affective and social-emotional aspects. The self-disclosure approach encourages students to express their thoughts, feelings, and personal experiences related to Islamic values, thus promoting deeper understanding and interaction in the classroom. This research employed a descriptive qualitative method using observation, reflective writing, and interviews as data collection techniques. The participants consisted of nine eighth-grade students of SMP Al-Hasra Depok and two teachers (a guidance and counseling teacher and a PAI teacher) who provided supporting information. Data analysis was conducted to describe students’ levels of openness and the impact of the self-disclosure technique on their interpersonal communication skills. The findings revealed that self-disclosure activities, such as reflective questioning, personal writing, and oral sharing, improved students’ confidence, emotional expression, and ability to relate personal experiences to Islamic teachings. Students’ openness levels were categorized into three types: Type 1 (courageous and reflective), Type 2 (reflective in writing but less active orally), and Type 3 (limited openness). Overall, the self-disclosure technique effectively strengthened interpersonal communication and fostered affective, spiritual, and social values in PAI learning. Keywords: Self-disclosure, interpersonal communication, Islamic Religious Education (PAI). Abstrak— Penelitian ini membahas penerapan teknik self-disclosure (keterbukaan diri) dalam pembelajaran Pendidikan Agama Islam (PAI) dan bagaimana teknik ini dapat meningkatkan kemampuan komunikasi interpersonal siswa. Pembelajaran yang efektif tidak hanya menekankan aspek kognitif, tetapi juga afektif dan sosial-emosional. Self-disclosure membantu siswa berani mengungkapkan perasaan, pengalaman, dan pendapat pribadi mereka dalam konteks pembelajaran yang bernilai islami. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, refleksi tertulis, dan wawancara. Informan terdiri atas sembilan siswa kelas VIII SMP Al-Hasra Depok serta dua guru (guru BK dan guru PAI) sebagai pendukung data. Data dianalisis untuk menggambarkan tingkat keterbukaan siswa serta dampak penerapan self-disclosure terhadap kemampuan komunikasi interpersonal mereka. Hasil penelitian menunjukkan bahwa penerapan teknik self-disclosure melalui kegiatan refleksi, penulisan pengalaman pribadi, dan penyampaian lisan mendorong keberanian siswa untuk berbicara, meningkatkan kemampuan mengekspresikan emosi, serta menghubungkan pengalaman pribadi dengan nilai-nilai Islam. Tingkat keterbukaan siswa terbagi menjadi tiga tipe, yaitu Tipe 1 (berani dan reflektif), Tipe 2 (reflektif dalam tulisan tetapi belum tampil lisan), dan Tipe 3 (masih terbatas dalam keterbukaan). Penerapan teknik ini berkontribusi positif dalam pengembangan komunikasi interpersonal sekaligus menanamkan nilai-nilai afektif, spiritual, dan sosial dalam pembelajaran PAI. Kata Kunci: Self-disclosure, komunikasi interpersonal, pembelajaran PAI.